2013
DOI: 10.3168/jds.2013-6699
|View full text |Cite
|
Sign up to set email alerts
|

Plane of nutrition during the preweaning period but not the grower phase influences the neutrophil activity of Holstein calves

Abstract: Two experiments were conducted to determine the influence of plane of nutrition during (1) the pre- and immediate postweaning periods and (2) the grower phase on the performance and leukocyte responses of Holstein calves. In experiment 1, 39 (2 ± 1 d old) colostrum-fed heifer calves were randomly assigned to 2 planes of nutrition, a low (LPN; n = 19) and a high plane of nutrition (HPN; n = 20). Calves in the LPN treatment were offered 418 g/d of dry matter (DM) of a 20% crude protein (CP)/20% fat milk replacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
24
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 31 publications
(45 reference statements)
11
24
2
1
Order By: Relevance
“…However, recently, variations in haptoglobin concentrations following weaning have been considered to be inconsistent and unreliable indicators of a stress response (O'Loughlin et al, 2014). Similar to that observed by Obeidat et al (2013), we observed a differential acute phase protein response between the two breeds employed and plane of nutrition had no effect on the acute phase response. This is in contrast to the findings of Ballou (2012) where calves fed a higher plane of MR nutrition had greater plasma haptoglobin concentrations following a lipopolysaccharide challenge than calves fed a lower plane of MR nutrition containing reduced DM and CP.…”
Section: Figuresupporting
confidence: 82%
“…However, recently, variations in haptoglobin concentrations following weaning have been considered to be inconsistent and unreliable indicators of a stress response (O'Loughlin et al, 2014). Similar to that observed by Obeidat et al (2013), we observed a differential acute phase protein response between the two breeds employed and plane of nutrition had no effect on the acute phase response. This is in contrast to the findings of Ballou (2012) where calves fed a higher plane of MR nutrition had greater plasma haptoglobin concentrations following a lipopolysaccharide challenge than calves fed a lower plane of MR nutrition containing reduced DM and CP.…”
Section: Figuresupporting
confidence: 82%
“…Ballou (2012) reported that neutrophil oxidative burst or whole-blood bactericidal capacity was not influenced by plane of MR nutrition during the preweaning period among either Jersey or Holstein calves. In contrast, Obeidat et al (2013) observed that Holstein calves fed a restricted quantity of MR had elevated neutrophil oxidative burst and surface expression of the adhesion molecule L-selectin compared with calves fed a greater amount of MR during the preweaning period (d 0-53). Those authors speculated that the greater neutrophil activity among the calves fed the reduced quantity of MR was a result of either less stress or increased microbial exposure due to more nonnutritive oral behaviors.…”
Section: Introductionmentioning
confidence: 67%
“…The data on fecal scores are equivocal; some studies showing that calves fed a greater quantity of milk had more loose feces (Nonnecke et al, 2003;Bartlett et al, 2006), whereas others report no differences in fecal scores (Ballou, 2012;Obeidat et al, 2013). Recently, Ollivett et al (2012) observed that feeding greater quantities of MR to calves reduced duration of scours and improved hydration and ADG following a Cryptosporidium parvum challenge at 3 d of age.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Healthy growth is crucial for young dairy calves because it determines the future profitability and sustainability of a dairy enterprise (Soberon et al, 2012;Obeidat et al, 2013). Activation of immune system has been related to the decrease of growth performance (Steiger et al, 1999;Sartin et al, 2011) and to disturb metabolism (Kimball et al, 2003) in animals.…”
Section: Introductionmentioning
confidence: 99%